Фізичні основи квантового комп’ютера - Книш, А. О. (ХНУРЕ, 2023)
This work will describe such physical foundations of a quantum computer as: superposition principle, quantum entanglement, quantum téléportation, interference; describes the advantages and differences of a quantum computer over a classical one, its prospects and areas of application, phenomena that complicate the process of its development and reduce its productivity, as well as ways to overcome them.